Effects of fartlek training and continuous run on selected physical fitness variable among inter Collegiate men students - T.ARUN PRASANNA,; DR.K.VAITHIANATHAN, (International Journal of Pharma and Bio Sciences, 2018)
The study aims to examine the effects of two training programs on selected physical fitness variables among college male students who involve in sports activities regularly. Thirty students were divided randomly into experimental group-I (n=15) and II (n=15) to undergo an intervention period of six weeks with fartlek training and continuous run respectively. The selected criterion variables namely speed endurance and cardio-respiratory endurance were conducted on the students before and immediately after the training using 300-meters run and Cooper's and 12-min run/walk fitness test respectively. The statistical analysis of the raw data on the selected fitness variables was done using t-test to determine whether both the groups differ significantly. The significance level to the test‘t’ ratio obtained was tested at the fixed confidence level of 0.05. The study revealed the occurrence of significant difference in the criterion variables among the two experimental groups.